Innovation Capacity as a Strategic Mediator: Linking Leadership Styles and Productivity in The Banking Sector - Andi Yusniar Mendo; Syamsul B. Biki; Mohammad Dimas Suronoto (Fundamental and Applied Management Journal, 2026)
The banking industry's rapid digital transition demands strong leadership and the capacity to innovate in order to boost productivity. Using organizational innovation capacity as a mediating variable, this study investigates the impact of transformational leadership and digital leadership on organizational productivity in the banking sector of Gorontalo Province, Indonesia. A quantitative approach was employed, surveying 300 bank employees, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the hypotheses. The findings reveal a differential mediation pattern that constitutes the study's central theoretical contribution: transformational leadership affects productivity both directly and indirectly through innovation capacity (partial mediation), whereas digital leadership affects productivity only indirectly through innovation capacity (full mediation). Specifically, digital leadership does not significantly influence productivity directly (H2: β = 0.003, p = 0.967), but its indirect effect via innovation capacity is significant (H7: β = 0.092, p = 0.002). Transformational leadership maintains a significant direct effect (H1: β = 0.397, p = 0.000) alongside its indirect path. Productivity is also directly and positively impacted by organizational innovation capacity (H5: β = 0.480, p = 0.000). Theoretically, this study offers a novel conceptual insight by demonstrating that in a regional banking context with moderate digital maturity, innovation capacity is a strategic necessity – without it, digital leadership remains ineffective in driving productivity. Practically, bank management should differentiate leadership development programs, conduct innovation readiness assessments before investing in digital leadership, align digital leadership KPIs with innovation metrics, and invest in innovation capacity as a strategic complement to digital leadership to ensure sustainable productivity gains.